Potensi Larvasida Tanaman Endemik Kalimantan terhadap Aedes aegypti: Tinjauan Evidensi Ilmiah dan Prioritas Kandidat Riset - Vincentia Ade Rizky; Maria Selviana Joni; Umi Latifah; Tri Astuti Sugiyatmi (Pusat riset dan Inovasi Nasional, 2026)
Dengue remains a major vector-borne disease worldwide, and the increasing resistance of Aedes aegypti to synthetic insecticides has encouraged the exploration of environmentally friendly botanical larvicides. This study aimed to systematically evaluate scientific evidence regarding the larvicidal potential of endemic Kalimantan plants against Aedes aegypti and to identify priority candidates for future research. A systematic literature review was conducted following the PRISMA 2020 guidelines. Literature searches were performed across Scopus, PubMed, ScienceDirect, SpringerLink, Web of Science, MDPI, Wiley Online Library, Garuda, SINTA, and Google Scholar for studies published between January 2016 and January 2026. A total of 925 records were identified, and after duplicate removal, screening, and eligibility assessment, 88 studies were included in the final synthesis. The results showed that botanical larvicides rich in alkaloids, flavonoids, terpenoids, phenolics, limonoids, and sulfur compounds demonstrated significant larvicidal activity against Aedes aegypti. However, no direct larvicidal studies were identified for endemic Kalimantan species, including Fibraurea tinctoria, Arcangelisia flava, Dacrydium beccarii, Agathis borneensis, and Scorodocarpus borneensis. These findings highlight substantial evidence gaps and indicate that Kalimantan biodiversity represents a promising source of novel larvicidal agents for sustainable dengue vector control.